Calcified Leiomyomata Presenting as Recurrent Pregnancy Loss - Mohammad Marwan Alhalabi; Ameer Kakaje; Marwan Alhalabi (Case Reports in Obstetrics and Gynecology)
Recurrent spontaneous abortion (RSA) is a problem that faces women for a variety of reasons. Although leiomyomata is relatively common, calcified leiomyomata which is called “womb stones” is a very rare cause of RSA. These womb stones are correlated with retained products from conception and osseous metaplasia. We report a very rare case of a large calcified leiomyomata which caused secondary infertility and pregnancy loss of 7 pregnancies due to spontaneous abortions.